2020
DOI: 10.1111/joca.12309
|View full text |Cite
|
Sign up to set email alerts
|

Quality‐of‐life as chronotopefication and futurization: Subsistence consumer experiences in India

Abstract: In the poverty‐ridden settings in neo‐liberal India, we explore how subsistence consumers construct their quality‐of‐life (QOL). Drawing on the concepts of chronotope and futurization, we posit two additional dimensions of subsistence consumers' construction of QOL namely, chronotopefication and futurization. Our findings suggest that chronotopefication and futurization are defining processes of subsistence consumers' construction of QOL perceptions; their sacrifices, efforts, and costs, however painful they m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 135 publications
0
5
0
Order By: Relevance
“…During this period, as the marketplaces of Global South crack under life circumstances that are precarious and extreme, the consumer concerns from these spaces reflect the marginal voices, deriving implications for a range of previously unaddressed topics, particularly of consumer affairs. While much of the existing literature about consumer well-being and consumer affairs of the subsistence marketplace explores such conditions under "normal" situations (Chaplin et al, 2014;Farrell & Hill, 2018;Hill, 2002;Hill & Adrangi, 1999;Jagadale et al, 2020), pandemics (particularly COVID-19) offers a fresh look at the "new normal" consumption from the margins of the Global South. Western neoliberal market policies and strategies, meant for the upliftment of the poor, already have their critics.…”
Section: The Context Of Pandemic and The Global Southmentioning
confidence: 99%
“…During this period, as the marketplaces of Global South crack under life circumstances that are precarious and extreme, the consumer concerns from these spaces reflect the marginal voices, deriving implications for a range of previously unaddressed topics, particularly of consumer affairs. While much of the existing literature about consumer well-being and consumer affairs of the subsistence marketplace explores such conditions under "normal" situations (Chaplin et al, 2014;Farrell & Hill, 2018;Hill, 2002;Hill & Adrangi, 1999;Jagadale et al, 2020), pandemics (particularly COVID-19) offers a fresh look at the "new normal" consumption from the margins of the Global South. Western neoliberal market policies and strategies, meant for the upliftment of the poor, already have their critics.…”
Section: The Context Of Pandemic and The Global Southmentioning
confidence: 99%
“…To address transformative goals through empowering subsistence‐level prosumers and bringing about increased well‐being, methods that privilege their knowledge systems are crucial (Viswanathan, Chakrabarti, et al, 2021; Viswanathan, Umashankar, et al, 2021). Therefore, a micro‐level bottom‐up approach is required that allows “views and voice from below” to inform the development of inclusive marketing systems, and effective public policy that reflects the subsistence populace's multilayered socio‐economic and cultural needs of the subsistence populace (Jagadale et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Subsistence marketplaces, where prosumers struggle daily to maintain necessities of life and socio‐cultural survival (Viswanathan and Sreekumar, 2019; Venugopal & Viswanathan, 2017, 2021), are of growing interest to marketing and consumer researchers (e.g., Hill & Martin, 2014; Jagadale et al, 2021; Venugopal & Viswanathan, 2021). Those living at the subsistence level and where large numbers of the population occupy the lowest level of the economic pyramid (Viswanathan, Chakrabarti, et al, 2021; Viswanathan, Umashankar, et al, 2021) are found in multiple geographical locations and cultures, usually in developing and emerging countries and especially those least developed (Viswanathan, Chakrabarti, et al, 2021; Viswanathan, Umashankar, et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…A central pillar of subsistence marketplace literature is the importance of thoroughly understanding the experiences of individuals and communities living in poverty and to map out the struggles these individuals face in meeting their basic needs (Jagadale et al, 2020). To capture the complexity inherent in poverty, subsistence marketplace studies use a bottom-up approach.…”
Section: Introductionmentioning
confidence: 99%